2022
DOI: 10.21931/rb/2022.07.04.610.21931/
|View full text |Cite
|
Sign up to set email alerts
|

Role of ascorbic acid and appetite stimulants on a few blood serum biochemical characteristics in pregnant Iraqi ewes under heat stress

Abstract: This study evaluated the effect of VêO® premium (2 or 4)g and ascorbic acid on pregnant ewes on some minerals. Twenty Iraqi ewes are aged 2-4 years in the Fallujah, Al-Anbar Government regions from August 5th, 2019, to February 9th, 2020. The ewes were divided randomly into four groups. It was fed naturally and on one diet, and the (G1) was given VêO® premium 4 g, (G2) was given VêO® premium 2 g, (G3) was given ascorbic acid 40 mg, and (G4) was treated as the control group. Blood samples were taken monthly via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…found a relationship between some variants of this MC4R gene with some reproductive characteristics, including fertility in goats Mishra et al [48]. Genetic and environmental factors play an essential role in livestock animals in terms of productive and economic traits, and thus are considered the basis for most of the important and productive traits in animal life [49,50,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…found a relationship between some variants of this MC4R gene with some reproductive characteristics, including fertility in goats Mishra et al [48]. Genetic and environmental factors play an essential role in livestock animals in terms of productive and economic traits, and thus are considered the basis for most of the important and productive traits in animal life [49,50,51,52].…”
Section: Resultsmentioning
confidence: 99%
“…Ginseng is a popular herbal medicine for relieving menopausal symptoms and was widely used as an alternative to hormone replacement therapy. Studies also showed that ginseng had strong estrogenic activity in OVX mice [30][31][32][33]. A study by [18] showed that the ginsenosides present in the ginseng plant have a protective and improving role in maintaining estrogen levels.…”
Section: Estrogen Concentrationmentioning
confidence: 99%
“…Korean according to the method recommended by the manufacturer. Using a pair of primers, ITS1 as a forward (F: 5′-TCCGTAG-GTGAACCTGCGG-3′) and ITS4 as a reverse (R: 5′TCCTC-CGCTTATTGATATGC-3′), the target region of the fusarium oxysporum was amplified using a polymerase chain reaction (PCR) polymerase chain reaction (PCR) device 14 .…”
Section: Molecular Diagnosis Of Fusarium Oxysporummentioning
confidence: 99%